2012
DOI: 10.1371/journal.pntd.0001482
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Virological Study of Dengue Cases and the Members of Their Households: The Multinational DENFRAME Project

Abstract: BackgroundDengue has emerged as the most important vector-borne viral disease in tropical areas. Evaluations of the burden and severity of dengue disease have been hindered by the frequent lack of laboratory confirmation and strong selection bias toward more severe cases.MethodologyA multinational, prospective clinical study was carried out in South-East Asia (SEA) and Latin America (LA), to ascertain the proportion of inapparent dengue infections in households of febrile dengue cases, and to compare clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 49 publications
3
45
0
Order By: Relevance
“…Previous studies examining variation in serotype detection by the Standard Diagnostics (24) and Panbio/Bio-Rad Platelia (12) NS1 ELISAs reported generally higher sensitivities than those presented here. Interestingly, the Bio-Rad and Standard Diagnostics NS1 antigen ELISAs had relatively low sensitivities for dengue virus serotype 2 compared to previously reported sensitivities of the Bio-Rad assay for the other serotypes (7), which is significant as serotype 2 is highly prevalent in both the Americas and Asia (1,8,10,21).…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies examining variation in serotype detection by the Standard Diagnostics (24) and Panbio/Bio-Rad Platelia (12) NS1 ELISAs reported generally higher sensitivities than those presented here. Interestingly, the Bio-Rad and Standard Diagnostics NS1 antigen ELISAs had relatively low sensitivities for dengue virus serotype 2 compared to previously reported sensitivities of the Bio-Rad assay for the other serotypes (7), which is significant as serotype 2 is highly prevalent in both the Americas and Asia (1,8,10,21).…”
Section: Discussionmentioning
confidence: 56%
“…Sensitivity of NS1 testing is directly related to the viral load, and thus the time since the start of viral replication: the mean duration of fever at the time of sampling was 2.4 days. Although the NS1 antigen test used in this study to test for laboratory-confirmed dengue has high specificity [18], [27], DENV-2 infections have been associated with significantly lower plasma NS1 levels relative to DENV-1 or DENV-3 infections [28]. In addition, a lower sensitivity for this test has been reported for secondary infections and, in dengue-endemic areas (such as those where this study was conducted), a higher proportion of patients have secondary infections [27].…”
Section: Discussionmentioning
confidence: 97%
“…In one of the first prospective dengue cohort studies in Bangkok, Thailand [9], and in a multinational index cluster study with four sites in South-East Asia and Latin America [14], the inapparent-to-symptomatic ratio was similar in primary and secondary infections. We also previously reported similar ratios in primary and secondary DENV infections in Managua, Nicaragua [15].…”
Section: Introductionmentioning
confidence: 94%